SISTEM PENGENDALIAN SUHU DAN KELEMBABAN PADA BILIK DISINFEKTAN BERBASIS BLYNK DENGAN MENGGUNAKAN NODEMCU ESP8266 - Daniel Bawer Simanjuntak; Bambang Widodo; Susilo Susilo; Stepanus stepanus; Judo Ignatius Nempung (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2021)
Coronavirus Disease 2019 (COVID-19) has been declared by WHO as a global pandemic and in Indonesia it is stated as a type of disease that causes public health emergencies and non-natural disasters, so it is necessary to make prevention efforts including prevention and control (Kemenkes RI, 2020) regarding prevention guidelines. and control of coronavirus disease 2019 (COVID-19). One way to prevent the spread of covid-19 is to spray disinfectants on objects suspected of having a virus. Especially for the human body, disinfectant spraying is carried out in a specially designed room or room. These booths are placed in markets, malls, schools, places of worship and so on. This research was conducted from September 2020 to December 2020 at the Faculty of Engineering, Christian University of Indonesia, Jakarta. Based on the test, it was found that the temperature and humidity can be displayed on the LCD and mobile phones via the Blynk application. Temperature regulation is done by activating or deactivating the exhaust fan and fan. At a temperature of> 280C the exhaust fan and fan will be active, then not active if the temperature is ≤280C. This tool has a measurement accuracy level for a temperature of 99.99% and 99.98% humidity with a thermohygrometer as a measurement reference tool.